Human Security from an Islamic Perspective: A Case Study of the 2023 Israel - Gaza War - Rahmatul Linsani; Sidik Jatmika (Ilomata International Journal of Social Science, 2026)
This study analyzes human security violations during the 2023 Israel–Gaza war using an Islamic Human Security Framework (IHSF) that integrates contemporary human security theory with maqāṣid al-sharīʿah (al-ḍarūriyyāt al-khams). Shifting from state-centered security, the framework redefines civilians as the primary referent object, identifies multidimensional threats, and derives ethical and policy implications grounded in both international norms and Islamic principles. Employing a qualitative document-based case study, this research examines 42 reports published between October 2023 and March 2024 by United Nations agencies (UN, UNRWA, OCHA), international human rights organizations, and peer-reviewed academic sources. Data were selected based on institutional credibility, temporal relevance, and cross-source verification, and analyzed through thematic content analysis with triangulation. The findings reveal systematic human security violations across five analytically mapped dimensions: protection of life (ḥifẓ al-nafs), evidenced by extensive civilian casualties; food security, indicated by siege-induced famine risks and obstruction of aid; health security, reflected in the destruction and paralysis of medical facilities; shelter and property protection (ḥifẓ al-māl), shown through large-scale housing destruction; and human dignity, manifested in forced displacement and collective punishment. Rather than assuming equivalence, the study explicitly aligns maqāṣid principles with modern human security dimensions, demonstrating their complementary evaluative capacity. The novelty of this research lies in operationalizing maqāṣid al-sharīʿah as normative criteria within a human security assessment of armed conflict. Limitations include reliance on secondary reports, contested casualty figures, and restricted access to field data.